Ecologies of crusading, colonization, and religious conversion in the medieval Baltic: Terra Sacra II - Pluskowski, Aleksander (Environmental histories of the North Atlantic world, 2019)
"In the thirteenth century, crusading armies unleashed a relentless holy war against the pagan tribal groups of the Eastern Baltic, whose territories were conquered and reorganized into Christian states run by the Teutonic Order, bishops, and their cathedral chapters. Castles were built, towns established, and colonists encouraged to settle under the leadership of the new Christian theocracy. But the changes introduced alongside Christianity not only transformed the culture of eastern Baltic societies, but also had a profound and -- for the Baltic tribes, who saw many aspects of the natural world as sacred -- deeply significant impact on the local environment. This seminal period in the environmental history of north-eastern Europe has been the focus of the ERC-funded research programme, 'The Ecology of Crusading', which explored the physical and conceptual ecological transformations associated with warfare, colonization, and religious conversion. This second Terra Sacra volume draws together a series of case-studies on Livonia and Prussia that provide a unique snapshot of recent research into environmental change during the Baltic Crusades and also explore long-term trends in landscape organization and environmental exploitation. The volume covers six key themes: building-construction in the conquered territories; food supply to the houses of the Teutonic Order; life in the multi-cultural towns of the eastern Baltic; transforming the physical landscape; transforming the spiritual landscape; and the Baltic Ordensland in its regional context. It forms a companion to Environment, Colonization, and the Baltic Crusader States: Terra Sacra I."-- Provided by publisher